Using Gross Trade Data to Map Archetypal GVCs - Ferrantino, Michael J.; Schmidt, Gabriela (World Bank, Washington, DC, 2018)
This paper introduces a new, publicly available database for tracking merchandise trade in the global value chains for apparel/textile/footwear, motor vehicles and parts, and electronics, developed originally for in-depth analysis at the country level. The data enable tracking of intermediate and final goods trade by country. Among other results, the study finds that East Asia and Pacific is the most global value chain–intensive region, and Sub-Saharan Africa is the least global value chain–intensive region. Final assembly of motor vehicles is significantly more sophisticated (takes place in higher income countries), while final apparel is the least sophisticated global value chain category and is geographically dispersed. In general, intermediate goods are more likely to be traded within regions, and final goods are more likely to be traded between regions. South Asia produces a large value of relatively unsophisticated global value chain exports, focusing on apparel and textiles; North American exports are the most sophisticated. Within categories, the degree of product sophistication varies markedly.